About the Spondylogenic-Venous Lumboishialgia - Smolko, D.; AlievК.; Ponomaryov, G.; SkorometsА. (Psychiatry, Neurology and Medical Psychology, 2016)
In this paper we examined 50 patients aged 27 to 65 years old with long pain in the spine when one of the low-lumbar hernia of intervertebral discs.Pain intensity was assessed using a questionnaire and the Roland-Morris questionnaire Osvestrovskogo about the violation of life when the pain in the lower back.We compared two groups of patients: having expressed clinic venous stasis in the lumbar spine, and without such a stalemate. The study of expression of pain in the lower lumbar disc hernia showed that both radicular and local pain (diskalgiya) was significantly more intense in patients with the presence of chronic venous insufficiency of the blood circulation in the lower part of the spine compared with those without such disease.The dynamics of pain were evaluated in the treatment of L-lysine aescinat.